Chronological development of environmental protection and sustainable development in Ethiopia: Systematic review - Tsegay Kahsay Gebrekidan; Muuz Gebretsadik Gebremariam; Meaza Kidane Teferi; Selama Gebreslassie Yebyo (Watershed Ecology and the Environment)
Sustainable development aims to meet the needs of the present generation without compromising the ability of future generations to meet their own needs. It encompasses the continuous growth of political, cultural, economic, social, and environmental sectors. This review investigates the historical progress and actions of sustainable development in Ethiopia by examining various published and unpublished documents, government reports, policies, and legislation. The findings highlight that Ethiopia, with a longstanding history of environmental protection practices such as establishing protected areas, soil and water conservation, and sanitation, has made notable progress, especially since the mid-1990s. The inclusion of environmental rights in the 1995 Constitution led to the development of comprehensive policies, strategies, proclamations, regulations, and guidelines for sustainable development. Despite these advancements, Ethiopia faces numerous environmental challenges, including land degradation, climate change, deforestation, pollution, and inadequate implementation of environmental policies. These issues are further complicated by political instability, financial constraints, a lack of skilled human resources, rapid population growth, traditional agricultural practices, and weak community awareness. However, opportunities for improvement exist. Ethiopia can enhance its environmental goals by utilizing hydropower, investing in solar and wind energy, promoting sustainable agriculture, and accessing international climate finance. Nevertheless, the actions taken by the government and individuals have been inconsistent and scattered, leading to unsuccessful efforts to achieve sustainable development. Moving forward, addressing these persistent challenges requires coordinated efforts, political stability, innovative solutions, and public involvement. Strengthening institutional arrangements, enhancing education and awareness, and fostering collaboration at all levels are essential steps toward achieving sustainable development and environmental protection in Ethiopia.